Functionalization of titanium using kr-12 peptide: antibacterial and osteogenic properties - Demirci, Emine Afra; Onder, Sakip; Acar, Tayfun; Buyuk, Nisa Irem; Sunar, Zeynep Selin; Kose, Gamze Torun (EMERALD GROUP PUBLISHING LTD, 2024)
Titanium implants are widely used in orthopedic and dental applications owing to their biocompatibility and mechanical stability. Nonetheless, they encounter significant challenges pertaining to infection and poor osteointegration. We investigated the feasibility of two different coating strategies for titanium with the antimicrobial peptide KR-12: direct binding via carbodiimide (CDI) chemistry and indirect attachment through a polydopamine (PDA) layer, comparing these approaches in a comprehensive study. This study assessed the immobilization efficiency, antibacterial efficacy, and osteogenic capability of both coating techniques. The findings indicated that PDA-mediated immobilization achieved greater KR-12 binding efficiency (36.80%) compared with direct covalent binding (24.08%) and enhanced antibacterial effectiveness against Staphylococcus aureus, with colony counts decreasing by 98% for the Ti-PDA-KR12 group and by 95% for the Ti-KR12 group compared to the control group. In vitro investigations utilizing rat bone marrow-derived mesenchymal stem cells (rBMSCs) demonstrated that PDA-KR12 coated surfaces markedly enhanced cell adhesion, proliferation, and osteogenic differentiation, as indicated by elevated alkaline phosphatase (ALP) activity, osteocalcin synthesis, and upregulation of osteogenesis-associated gene markers. Our findings indicate that PDA-mediated peptide immobilization is a superior approach for augmenting both the antibacterial characteristics and osteogenic potential of titanium implants, presenting a possible method to enhance implant performance.
Keywords: antimicrobial peptide; titanium; surface modification; polydopamine; HUMAN CATHELICIDIN LL-37; ANTIMICROBIAL PEPTIDES; COVALENT IMMOBILIZATION; IMPLANTS; BACTERIAL; ADHESION; CHEMISTRY; INFECTION; COATINGS; Materials Science